First documentation of mangrove-associated gastropods highlights the status of early mature stands in the mangrove ecosystem of Pramuka Island, Jakarta Bay, Indonesia - YASMAN YASMAN; MBARA CHAM (Society for Indonesian Biodiversity, 2025)
Abstract. Yasman, Cham M. 2025. First documentation of mangrove-associated gastropods highlights the status of early mature stands in the mangrove ecosystem of Pramuka Island, Jakarta Bay, Indonesia. Biodiversitas 26: 1453-1460. This study examined the gastropod community in the Pramuka Island mangrove ecosystem, Jakarta Bay, Indonesia, focusing on species composition, ecological indices, and the influence of abiotic factors across different mangrove zones. A total of five gastropod species associated with mangroves were identified, with Cerithium coralium and Terebralia palustris being the most frequent and abundant. The presence of T. palustris, Telescopium telescopium, Nerita planospira, and C. coralium marks the first recorded occurrence of these species in the Pramuka Island mangrove ecosystem. The ecological indices revealed low diversity (H': 0.57), low evenness (E: 0.35), and high dominance (C: 0.78), thereby indicating an imbalanced gastropod community. These findings suggest that the island’s mangrove ecosystem is in the early stages of maturity in the form of a planted mangrove habitat. Abiotic parameters, including temperature, pH, salinity, and light intensity, were assessed, with light intensity showing significant variation between areas inside and outside the mangrove canopy. While other abiotic factors remained relatively stable, gastropod distribution appeared to be more influenced by feeding preferences and resource availability than by differences in light intensity. These results highlight the importance of understanding the ecological dynamics of mangrove-associated gastropods and their interactions with environmental factors, providing valuable insights for future mangrove restoration and management efforts.